THE ANXIETY FACTORS IN DELIVERING SPEECHES FOR INFORMATICS ENGINEERING STUDENTS - Swantika, Ika; Harissandi, Refin; Anwar, Rossya Diva (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Anxiety is one of the issues that individuals frequently encounter at various times. Everyone has likely felt anxiety at some point. An example of anxiety we frequently come across is the fear of interacting with others or speaking in front of an audience, particularly during a speech presentation. Students of STMIK Pelita Nusantara are required to be able to do public speaking, they should deliver material well when giving a speech, this is proven by the existence of a Public Speaking course that must be taken by students, but there are some students are unable to deliver a speech well. /This is shown by the reality that 60% of students continue to receive scores below the top marks in the public speaking course. This research seeks to identify the elements that lead to anxiety during public speaking, focusing on a group of 50 Informatics Engineering students by employing total sampling and utilizing questionnaires and surveys for data collection. There are 22 elements that lead to anxiety when delivering public speeches, particularly speeches. The 22 factors were condensed into 5 factors that students most frequently identified as the causes of their anxiety. Factor 1 includes the variables: time of day, morning, evening, and indoor display. Factor 2 includes the variables: negative thoughts, low self-esteem, interference from tools, negative prior experiences, absence of self-confidence, limited experience, and outdoor performance. Factor 3 includes the variables: absence of dialogue with specialists, apprehension about assessment, consciousness of being under scrutiny, and audience size. Factor 4 includes variables such as insufficient preparation, inadequate understanding of the subject, age variations, and poor health. Factor 5 includes variables such as religious variance, ethnic diversity, and insufficient proximity to expert